(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
In many economies, a significant proportion of service production is organized within market system. In the market system, the units in this organization base their economic activities on profit and benefit maximization. However, in most parts of service sector, pure competition conditions may not be valid. Health services are different from the goods which are produced and distributed by the open market. While some activities which are within the scope of health services are close to the definition of public, most of them have the characteristics of semipublic goods and services. Considering the importance which the mentioned services have regarding the society with their social benefits and the social costs which they will cause unless they are produced sufficiently, it could be argued that besides the open market, the public should also produce these services. The aim of this study is to present the insufficiency of market system in producing health services and analyze the intervention methods of public in order to compensate the insufficiency.